Evaluation of different methods for extraction of nanocellulose from yerba mate residues. (15th August 2019) - Dahlem, Marcos Aurélio; Borsoi, Cleide; Hansen, Betina; Catto, André Luís
Graphical abstract: Highlights: Reuse of an abundant renewable waste that are the yerba mate sticks (YMS). Evaluation and obtaining of cellulose nanofibres (CNF) from YMS. Use of chemical and mechanical treatments (steam explosion) to obtain CNF. Possibility of reduction in steps for obtaining nanocellulose from YMS. Difference in CNF morphology and size when used steam explosion. Abstract: In this work, we evaluate the production of nanocellulose from yerba mate sticks (YMS) using soft chemical and steam explosion treatments. The nanocellulose is characterized by chemical characterization, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), dynamic light scattering (DLS), transmission electron microscopy (TEM) and atomic force microscopy (AFM). The main results showed that after the chemical treatment and steam explosion, the YMS fiber reached diameters of 11–15 nm and aspect ratios (L/D) of 12–24. The XRD results showed that there is an increase in the index of crystallinity of up to 35% when compared to raw YMS. We discover that it is possible to obtain cellulose nanofibers (CNF) from the YMS without the use of alkaline treatment, which reduces the generation of liquid waste. Thus, the production of CNF by means of acid hydrolysis, bleaching and steam explosion represents an alternative route.